2016
DOI: 10.1098/rsta.2015.0044
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic temperature assignment to the point of inflection of the melting curve of high-temperature fixed points

Abstract: The thermodynamic temperature of the point of inflection of the melting transition of Re-C, Pt-C and Co-C eutectics has been determined to be 2747.84 ± 0.35 K, 2011.43 ± 0.18 K and 1597.39 ± 0.13 K, respectively, and the thermodynamic temperature of the freezing transition of Cu has been determined to be 1357.80 ± 0.08 K, where the ± symbol represents 95% coverage. These results are the best consensus estimates obtained from measurements made using various spectroradiometric primary thermometry techniques by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 48 publications
(72 reference statements)
2
90
0
Order By: Relevance
“…HTFP cells have been circulated among five partners over a period of more than one year and have shown that they can be considered as suitable means to probe and compare the capabilities between different realisations of the scale or of thermodynamic temperatures as the WP1 of InK has already proved [13].…”
Section: Preliminary Results and Discussionmentioning
confidence: 99%
“…HTFP cells have been circulated among five partners over a period of more than one year and have shown that they can be considered as suitable means to probe and compare the capabilities between different realisations of the scale or of thermodynamic temperatures as the WP1 of InK has already proved [13].…”
Section: Preliminary Results and Discussionmentioning
confidence: 99%
“…HTFP cells have been circulated among five partners over a period of more than one year and have shown that they can be considered as suitable means to probe and compare the capabilities between different realisations of the temperature scale or of thermodynamic temperatures as the WP1 of InK has already proved [13].…”
Section: Preliminary Findings and Discussionmentioning
confidence: 99%
“…-LNE-Cnam applied a similar scheme as CEM, which involved the calibration of the LNECnam LP3 pyrometer, except that the HTFP cells used were directly measured in terms of thermodynamic temperature using the LNECnam radiance method put in application in the WP1 of InK [13]. The cells used for the calibration of LNE-Cnam LP3 pyrometer had the local assigned thermodynamic temperatures as given in Table 3.…”
Section: Dissemination Using Absolutely Calibrated Filter Radiometersmentioning
confidence: 99%
“…Single-wavelength absolute radiometry has been successfully and extensively used over the last two decades to measure the temperature of the phase transitions of HTFPs. Recent results on Re-C cells are for example given in [2].…”
Section: Single-wavelength Absolute Radiometrymentioning
confidence: 99%
“…The currently ongoing improvements to the high-temperature range of the ITS-90, i.e., the development of novel high-temperature fixed points (HTFP) and their formal implementation into an improved temperature scale with the mise en pratique for the definition of the kelvin, rely solely on thermodynamic temperature measurements based on singlewavelength absolute radiometry traceable to the cryogenic radiometer (CR) [2]. The wording "single-wavelength" for a narrow band filter radiometer is used to distinguish from "double-wavelength method".…”
Section: Introductionmentioning
confidence: 99%